2020
DOI: 10.1097/md.0000000000023177
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for aspiration pneumonia in patients with dysphagia undergoing videofluoroscopic swallowing studies

Abstract: Prediction of aspiration pneumonia development in at-risk patients is vital for implementation of appropriate interventions to reduce morbidity and mortality. Unfortunately, studies utilizing a comprehensive approach to risk assessment are still lacking. The objective of this study was to analyze the clinical features and videofluoroscopic swallowing study (VFSS) findings that predict aspiration pneumonia in patients with suspected dysphagia. Medical records of 916 patients who underwent VFSS betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…37 Evidence from previous research findings have also revealed fluid penetration and aspiration status as important risk factors for all-cause mortality when conducting instrumental swallowing evaluations in patients with PSD. 38 Our study reported no difference in reducing aspiration/penetration among the combined and single neurostimulation and traditional dysphagia therapies possibly due to limited number of included studies for aspiration/penetration in the current NMA. Thus, more future studies are needed to address this issue and further investigation towards the mortality rate, incidence of aspiration pneumonia, and nutritional status among patients with PSD will be essential.…”
Section: Effectiveness Of Neurostimulation and Traditional Dysphagia ...contrasting
confidence: 53%
“…37 Evidence from previous research findings have also revealed fluid penetration and aspiration status as important risk factors for all-cause mortality when conducting instrumental swallowing evaluations in patients with PSD. 38 Our study reported no difference in reducing aspiration/penetration among the combined and single neurostimulation and traditional dysphagia therapies possibly due to limited number of included studies for aspiration/penetration in the current NMA. Thus, more future studies are needed to address this issue and further investigation towards the mortality rate, incidence of aspiration pneumonia, and nutritional status among patients with PSD will be essential.…”
Section: Effectiveness Of Neurostimulation and Traditional Dysphagia ...contrasting
confidence: 53%
“…Dysphagia develops in over half of patients with acute stroke [ 1 ]. Dysphagia is a major risk factor for aspiration pneumonia in stroke patients [ 2 ]. The incidence of aspiration pneumonia in stroke patients with dysphagia is reported to be 20–47% [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] The proportion of people with risk factors for AP is increasing. [20][21][22][23] AP is consistently associated with older age. 20 24-27 Up to a quarter of care home residents are at risk for AP at any given time.…”
Section: Continuedmentioning
confidence: 95%
“…Abnormal swallowing is caused by a variety of neurological, muscular or GI disorders and is unequivocally associated with increased risk of AP 17–19. The proportion of people with risk factors for AP is increasing 20–23…”
Section: Epidemiologymentioning
confidence: 99%